2021
DOI: 10.3389/fcell.2021.623753
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia Formation Does Not Rely on WNT/β-Catenin Signaling

Abstract: Primary cilia act as crucial regulators of embryo development and tissue homeostasis. They are instrumental for modulation of several signaling pathways, including Hedgehog, WNT, and TGF-β. However, gaps exist in our understanding of how cilia formation and function is regulated. Recent work has implicated WNT/β-catenin signaling pathway in the regulation of ciliogenesis, yet the results are conflicting. One model suggests that WNT/β-catenin signaling negatively regulates cilia formation, possibly via effects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…MAPK15 was reported to localize to the basal bodies of motile [ 8 ] and primary cilia [ 7 ] in vertebrates and to regulate their formation. Indeed, interfering with MAPK15 expression in both RPE1 ( Figure 1 a and Figure S1a ) and IMCD3 ( Figure 1 b and Figure S1b ) cells, two established models for studying primary ciliogenesis [ 27 , 28 ], respectively in human and murine cells, strongly inhibited their ability of assembling primary cilia. Interestingly, Kazatskaya et al recently showed that a MAPK15 kinase-dead mutant was not able to rescue siRNA-dependent inhibition of primary cilia formation in RPE1 cells [ 7 ], suggesting a key role for MAPK15 kinase activity in regulating this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK15 was reported to localize to the basal bodies of motile [ 8 ] and primary cilia [ 7 ] in vertebrates and to regulate their formation. Indeed, interfering with MAPK15 expression in both RPE1 ( Figure 1 a and Figure S1a ) and IMCD3 ( Figure 1 b and Figure S1b ) cells, two established models for studying primary ciliogenesis [ 27 , 28 ], respectively in human and murine cells, strongly inhibited their ability of assembling primary cilia. Interestingly, Kazatskaya et al recently showed that a MAPK15 kinase-dead mutant was not able to rescue siRNA-dependent inhibition of primary cilia formation in RPE1 cells [ 7 ], suggesting a key role for MAPK15 kinase activity in regulating this process.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the role of MAPK15 in primary cilia biogenesis, we, therefore, decided to investigate a potential role for this kinase in HH signaling. At this scope, we first tested MAPK15-dependent primary cilia formation in NIH3T3 cells, which is a well-established model for the study of both the HH pathway [ 25 ] and of ciliogenesis [ 27 ]. To modulate MAPK15 expression in these cells, we decided to use the stable expression of shRNAs for this kinase ( Figure S2 ) and demonstrated that this approach strongly reduced starvation-dependent primary ciliogenesis in these cells ( Figure 2 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…For all experiments, ΔFZD 1-10 HEK293T cells were used if nothing else was stated. ΔFZD 1-10 HEK293T cells ( 43 ) and ΔLRP5/6 HEK293 T-Rex cells ( 44 ) were cultured in DMEM (HyClone SH30081) supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin (Thermo Fisher Scientific 10270106 and 15140) in a humidified incubator at 37 °C and 5% CO 2 . All cell culture plastics were from Sarstedt unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…In the former case, use healthy cells, consider thawing a low passage aliquot of the cells, and check routinely for Mycoplasma. In addition, to promote ciliogenesis, try to optimize the cell density, length of serum starvation period, or consider using small molecules promoting cilia formation (e.g., Cytochalasin D ( Bernatik et al., 2021 ; Kim et al., 2010 )). In case the cilia presence is DOX-inducible (i.e., in the case of rescue experiment), we observed that adding DOX already 1–2 days prior to seeding the cells for imaging experiment results in a better rescue effect.…”
Section: Troubleshootingmentioning
confidence: 99%